Evaluation of virucidal activity of a few physicochemical agents against goat-pox virus - Bhatia, S S; Soman, J P (The Indian Journal of Animal Sciences, 2012)
Physico-chemical agents. viz. formalin (4%), sodium hypochlorite (0.4%), sodium hydroxide (4%), hydrochloric acid(0.4%), phenol (2%) sunlight and environmental temperatures (summer and winter), were examined against goat-poxvirus for virucidal activity. Formalin and phenol completely inactivated the virus in 10 min, whereas hydrochloric aciddid so in 30 min. Sodium hypochlorite failed to inactivate the virus in 30 min as there was only one log fall in residualtitre. Sunlight inactivated the virus in 60 min. The rate of inactivation was faster at 45°C (summer temperature) ascompared to the winter temperature (25°C-27°C) though the residual virus was recovered at the both temperatures after180 min exposure. On the basis of the results obtained, phenol in 2% concentration can be recommended for disinfectinggoat premises during goat-pox infection. Phenol is cheap, easily available and less irritant to tissues as compared toformalin.